Faktor Determinan Perilaku Keluarga Berncana (KB) Dengan Metode Operasi Pria (MOP) Di Kecamatan Jenawi Kabupaten Karanganyar - Purwanto, Andrias Heru; , Yuli Kusumawati, SKM., M.Kes s (2017)
Men have a role to use contraception with Operation Method Man (MOP). This was proven because the majority of women experience a mismatch in the use of contraception. KB MOP also has many advantages, in terms of cost to MOP KB relatively inexpensive, and KB was also secure, fast, and can last a lifetime. This study aims to determine Determinant factor Behaviour KB Operating Method Man (MOP) In District Jenawi Karanganyar. This study was observational with case control study design, population in this study 90 respondents 60 cases and 30 controls, by using research analysis chi-square test. The results showed that there was a relationship between knowledge and behavior KB MOP (p = 0.060), attitude and behavior of KB MOP (p = 0.001), family support with behavioral KB MOP (p = 0.000). Determinant factor Behaviour Operation Method Man (MOP) In District Karanganyar Jenawi most influential was family support.